2010
DOI: 10.1111/j.1600-079x.2009.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of apoptosis by melatonin in VSC4.1 motoneurons exposed to oxidative stress, glutamate excitotoxicity, or TNF-α toxicity involves membrane melatonin receptors

Abstract: Loss of motoneurons may underlie some of the deficits in motor function associated with CNS injuries and diseases. We tested whether melatonin, a potent antioxidant and free radical scavenger, would prevent motoneuron apoptosis following exposure to toxins and whether this neuroprotection is mediated by melatonin receptors. Exposure of VSC4.1 motoneurons to either 50 μM H 2 O 2 , 25 μM glutamate (LGA), or 50 ng/ml tumor necrosis factor-alpha (TNF-α) for 24 h caused significant increases in apoptosis, as determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 45 publications
9
75
0
2
Order By: Relevance
“…In fact, the inhibiting actions of melatonin on H 2 O 2 -induced apoptosis was abolished by the addition of the MT1/MT2 melatonin receptor antagonist luzindole to the incubation medium, whereas the addition of the specific MT2 antagonist 4P-PDOT was incapable of altering the protective effects of melatonin. In this regard, previous reports have described that melatonin antagonizes apoptosis via membrane melatonin receptors in several cell types (23,31). We have also found that the ERK defense pathway is likely to have a role in the protective actions of melatonin on sperm apoptosis.…”
Section: Discussionmentioning
confidence: 61%
“…In fact, the inhibiting actions of melatonin on H 2 O 2 -induced apoptosis was abolished by the addition of the MT1/MT2 melatonin receptor antagonist luzindole to the incubation medium, whereas the addition of the specific MT2 antagonist 4P-PDOT was incapable of altering the protective effects of melatonin. In this regard, previous reports have described that melatonin antagonizes apoptosis via membrane melatonin receptors in several cell types (23,31). We have also found that the ERK defense pathway is likely to have a role in the protective actions of melatonin on sperm apoptosis.…”
Section: Discussionmentioning
confidence: 61%
“…In particular, a variety of therapies have been studied to alter neuro-inflammation [1, 1214], reduce free radical damage[1517], reduce excitotoxic damage to neurons [18, 19], improve blood flow [20, 21], and counter the effects of local ionic changes [2125]. Previous investigations from our laboratories indicated increased intracellular free Ca 2+ levels, increased proteolytic activity, degradation of myelin and cytoskeletal proteins, granular degeneration of axons, and vesiculation of myelin all of which contribute to secondary injury and propagation of SCI [12, 17, 2628]. …”
Section: Preclinical Researchmentioning
confidence: 99%
“…Even though the mechanisms through which melatonin stimulates these signal transduction pathways have been extensively studied [12][13][14][15][16][17][18][19][20][21], little is known about the resulting cellular effects: MT1/MT2 receptors have been shown to mediate melatonin-dependent decrease of tumor cell proliferation [22] and anti-apoptotic effects [23][24][25]; MT1 seems to be responsible for the general response to photoperiodic signals [26].…”
Section: Melatonin Synthesis and Its Targetsmentioning
confidence: 99%